Administrative logic of grassroots community epidemic prevention from the perspective of attention allocation: evidence from Wuhan City - Zhang, Yanhua; Xu, Zuying; Xu, Jiaxi (Frontiers in Public Health, 2025)
BackgroundChinese grassroots governments utilize fewer administrative resources to carry out tasks assigned by higher levels of government. They have refined their attention allocation into two dimensions: intensity and span, and have developed different action models for routine and non-routine tasks. This management style is becoming increasingly common in Chinese grassroots government operations.MethodsThis paper presented a multiple case study of policy practices in Wuhan City, Hubei Province. The study analyzed the attention allocation practices of China’s grassroots government in high-pressure situations, particularly during the COVID-19 outbreak.ResultsGrassroots governments can conserve attention resources by allocating attention efficiently and flexibly to deal with the dilemma of ‘too many tasks with too little power’. We summarized three models of coping by grassroots governments: (1) Attention allocation model in routine tasks; (2) Attention model in non-routine tasks; and (3) Routinization model through attention diversion.ConclusionThis paper presented a framework for explaining grassroots government behavior from an attention allocation perspective. We also identified some limitations of this model, both as a complement to attention allocation research and for a better understanding of grassroots government behavior in China.